Sistem Pendukung Keputusan Pemilihan Kamera DSLR Dengan Metode Promethee - Alfonsius Lorensius; Diah Arifah Prastiningtyas; Febry Eka Purwiantono (LPPM STIKI MALANG, 2019)
Digital Camera Single Lens Reflex (DSLR) is a camera with a digital system that uses a single lens mounted on the camera body. All DSLR camera brands divide their consumers in camera user classes to make it easier for users to distinguish features, such as entry-level classes, professional classes (semi-professional & professional) and middle-class (semi-advanced & advanced). The choice of DSLR cameras for consumers has quite a number of parameters that can be used as a benchmark for someone to determine which DSLR camera fits their needs and desires. Parameters used in determining DSLR cameras can be subjective judgments or objective judgments. Sometimes someone has difficulty in determining the parameters taken in determining the decision, so the choices taken in the end are not exactly what is expected. Promethee method is one of determining the order (priority) in multicriteria analysis. Simplicity, clarity and stability are the main focus of problems in the promethee method. Like most other methods, the ranking process is done by selecting several alternatives with predetermined criteria. There are nine criteria to be tested, namely: image resolution, video resolution, ISO, focus point, screen pixel, shutter speed, battery life, camera class and price. Selection of Decision Support System Applications DSLR cameras are made with web-based programming languages PHP and MySQL as database management system software. This system is expected to provide DSLR camera recommendations in accordance with the criteria determined by prospective customers efficiently and effectively, so as to minimize the possibility of losses obtained by consumers.